2017
DOI: 10.1152/japplphysiol.00983.2016
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow regulation and oxygen uptake during high-intensity forearm exercise

Abstract: The vascular strain is very high during heavy handgrip exercise, but the intensity and kinetics to reach peak blood flow, and peak oxygen uptake, are uncertain. We included 9 young (25 ± 2 yr) healthy males to evaluate blood flow and oxygen uptake responses during continuous dynamic handgrip exercise with increasing intensity. Blood flow was measured using Doppler-ultrasound, and venous blood was drawn from a deep forearm vein to determine arteriovenous oxygen difference (a-vO) during 6-min bouts of 60, 80, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
27
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 53 publications
9
27
3
Order By: Relevance
“…The subject then performed rhythmic work for 6 min, and work efficiency data were collected within the final minute of this exercise period. In combination, a prior study (36) and a pilot study showed that blood gas and forearm blood flow measurements reached a plateau, defined as no change in V O2 over time (3), the final 2-3 min of the test. Position, contraction range of motion, and frequency were identical to that of the WR max test.…”
Section: Subjectsmentioning
confidence: 91%
See 1 more Smart Citation
“…The subject then performed rhythmic work for 6 min, and work efficiency data were collected within the final minute of this exercise period. In combination, a prior study (36) and a pilot study showed that blood gas and forearm blood flow measurements reached a plateau, defined as no change in V O2 over time (3), the final 2-3 min of the test. Position, contraction range of motion, and frequency were identical to that of the WR max test.…”
Section: Subjectsmentioning
confidence: 91%
“…Although a-vO 2diff was calculated indirectly from pulmonary V O 2 , the proposal may be reasonable as several differences in vascular and metabolic responses exist between arm and leg exercise (8,9,35). A pivotal impediment in arms (36,44) compared with legs is the larger influence from muscle contractions, resulting in a substantial hindrance to blood flow. This may be decisive for blood flow as an adapting mechanism in arms, and a-vO 2diff may thus be the regulated component in the oxygen supply and demand interplay after arm MST.…”
Section: Introductionmentioning
confidence: 99%
“…The coefficient of variation (CV) for the blood viscosity duplicates was <4%; the CV values did not vary according to the specific shear rate. The shear rates selected are within the physiological range documented for the brachial artery in humans at rest and during rhythmic handgrip exercise, based on pilot testing in our laboratory and previous literature using a similar exercise protocol (Nyberg et al., ). All blood viscosity measurements were performed at a standardized temperature of 37°C with the use of a circulating heated water bath.…”
Section: Methodsmentioning
confidence: 99%
“…To this end, we used high‐resolution Duplex ultrasound and serial venous blood samples draining the forearm for the assessment of brachial artery shear rate and blood viscosity, respectively. We measured blood viscosity in vitro across 10 discrete shear rates (75–1500 s −1 ) spanning the physiological range documented for the brachial artery in basal and exercise conditions (Nyberg, Berg, Helgerud, & Wang, ). Subsequently, we modelled the non‐Newtonian behaviour of blood via a two‐phase exponential decay to obtain a direct estimate of the viscosity corresponding to the ultrasound‐derived brachial artery shear rate to evaluate the shear stress response.…”
Section: Introductionmentioning
confidence: 99%
“…Blood flow during rhythmic exercise is bi-phasic in nature, plateauing (e.g. steady-state) within a few minutes of the onset of exercise (212,242,251,252,(267)(268)(269). The kinetic response of blood flow and vasodilation may be separated into three distinct phases.…”
Section: Feed-forward To Dynamic Exercisementioning
confidence: 99%